Enzymatic biodiesel production from sludge palm oil (SPO) using locally produced Candida cylindracea lipase - Nasaruddin, Ricca Rahman; Alam, Md Zahangir; Jami, Mohammed Saedi (Academic Journals, 2013)
Biodiesel is a non-toxic, renewable and environmental friendly fuel. This study involved the production of biodiesel from sludge palm oil (SPO), a low-cost waste oil via enzymatic catalysis. The enzyme catalyst was a Candida cylindracea lipase, locally-produced using palm oil mill effluent as the low cost based medium. The results in solvent system for biodiesel production showed that ethanol gave higher yield of biodiesel as compared to methanol. One-factor-at-a time (OFAT) method was applied to investigate several factors for enzymatic biodiesel production. The optimum levels of ethanol-to-SPO molar ratio, enzyme loading, reaction temperature, mixing speed and reaction time were 4:1, 10 U, 40°C, 250 rpm and 24 h, respectively with maximum yield of biodiesel of 62.3% (w/w SPO). The SPO had a promising potential for enzymatic biodiesel production using locally-produced lipase